2019
DOI: 10.1007/s00228-018-02614-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma and oral fluid concentrations of mycophenolic acid and its glucuronide metabolite by LC-MS in kidney transplant patients

Abstract: Purpose Mycophenolic acid is one of the most used immunosuppressive drugs in solid organ transplant treatments in the world. Developing a highly sensitive analytical method to analyse the drug and its metabolites in oral fluid and plasma is important to evaluate the possibility of using oral fluid as a biological matrix in therapeutic drug monitoring, instead of plasma. Method The liquid chromatography coupled to mass spectrometry (LC-MS) method was developed and validated for determining mycophenolic acid (MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 31 publications
2
16
3
Order By: Relevance
“…These issues taken collectively are likely responsible for the very conflicting results generated using oral fluid in the clinical setting. Some studies reported an acceptable correlation of total as well as fMPA concentrations between plasma and oral fluid concentrations, 266,267,351 whereas others found a poor correlation. 350 Therefore, the use of oral fluid for the purpose of MPA TDM cannot be recommended yet, and further studies are needed to identify the most appropriate sampling and sample pretreatment conditions.…”
Section: Oral Fluidmentioning
confidence: 99%
“…These issues taken collectively are likely responsible for the very conflicting results generated using oral fluid in the clinical setting. Some studies reported an acceptable correlation of total as well as fMPA concentrations between plasma and oral fluid concentrations, 266,267,351 whereas others found a poor correlation. 350 Therefore, the use of oral fluid for the purpose of MPA TDM cannot be recommended yet, and further studies are needed to identify the most appropriate sampling and sample pretreatment conditions.…”
Section: Oral Fluidmentioning
confidence: 99%
“…As the values of tMPA pharmacokinetics were shown to be higher in children with nephrotic syndrome [3][4][5], we analyzed the linearity of the method over a wide range and with a higher upper limit (5-2000 ng/mL) than in other literature studies. Our method meets the requirements for within-run and between-run accuracy and precision, with the sMPA LLOQ being 5 ng/mL, which is the same as in one study in the literature [22]. Generally, LC-MS/MS methods are more sensitive and show lower LLOQ, with values of 2.5 ng/mL [19], 2 ng/mL [16], 1.6 ng/mL [20], and 1 ng/mL [15].…”
Section: Discussionmentioning
confidence: 52%
“…However, more recently, two studies have reported contradictory results [15,21]. All studies on salivary MPA (sMPA) have employed liquid chromatography tandem mass spectrometry (LC-MS/ MS) for sMPA determination [8,15,16,19,20,22], but none have used high-performance liquid chromatography with fluorescence detection (HPLC-FLD). The HPLC-FLD method may have some advantages, such as lower analysis cost and greater availability of HPLC equipment than LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 22 Besides plasma, as the most used fluid for drug monitoring, saliva is assumed to be more suitable for the pharmacometric approach, regarding its non invasive, cost‐effective and friendly‐time consuming sampling and not requiring trained personnel, particularly for unbound drugs monitoring. 23 , 24 Therefore, question that has risen is how to mark a moment or patient when saliva becomes an optimal biological material. Still, this question is related with an effort for clarification of factors that might influence MPA plasma‐saliva relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, therapeutic drug monitoring might be useful in reducing interindividual variability in MPA exposure, optimizing immunosuppressive therapy and avoiding graft rejection in routine clinical practice 16,22 . Besides plasma, as the most used fluid for drug monitoring, saliva is assumed to be more suitable for the pharmacometric approach, regarding its non invasive, cost‐effective and friendly‐time consuming sampling and not requiring trained personnel, particularly for unbound drugs monitoring 23,24 . Therefore, question that has risen is how to mark a moment or patient when saliva becomes an optimal biological material.…”
Section: Introductionmentioning
confidence: 99%